Fuzzy Analytical Hierarchy Process Evaluation of Stakeholder Groups Involvement in Forest Management Situations - GRAZHDANI, Dorina (Journal of Environmental Management and Tourism, 2024)
Decision-makers frequently face numerous complex, unforeseen, and irreversible problems when choosing forest management for a given situation. In these kinds of circumstances, a multitude of stakeholders or interest groups may be involved, and it may be necessary to consider a variety of criteria. In a case study of Prespa Park, we employed an approach that integrates the Fuzzy Analytical Hierarchy Process (FAHP), extended goal programming (ExtGoalProg), and "Saaty-type" surveys to rank five forest management scenarios selected through a participatory process. We also looked at three techniques for normalizing stakeholder preferences to see if they affected FAHP scenario rankings. The study was based on different empirical analyses and conducted in three parts. The first part involved identifying the key stakeholders involved in the process, establishing the "stakeholders' panel," dividing it into four "interest groups," and creating a "study/professional panel." The next step involved the identification of five alternative forest management scenarios and their associated criteria. The second part involved applying the FAHP-ExtGoalProg approach, which combines FAHP and ExtGoalProg , to rank the scenarios. In the third part of this study, we looked at how the ExtGoalProg, geometric mean, and weighted arithmetic mean techniques compared when it came to combining the preferences of different stakeholders into a single preference for all five forest management scenarios. The techniques produced varying scenario rankings, indicating that stakeholders should consult and consider the situation before selecting the optimal normalization technique to prevent bias or misleading results. The suggested approach is suitable for addressing comparable issues in forestry and environmental management.